ALAM UMPSA Community Programme Phase 2 plants 300 trees in Rimba Lestari - Nurul Farhanah, Mohamad Idres (UMPSA, 2024)
PEKAN, 21 June 2024 – In raising awareness about the importance of forests for well-being and quality of life in addition to efforts to improve ecosystems and biodiversity, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) organised the ALAM UMPSA Community Programme Phase 2 to foster the spirit of love for nature.